O možnih spremembah pravne ureditve gospodarjenja z gozdovi v zasebni lasti - Pucelj Vidović, Tanja (Javna uprava, 2023)
There are several factors contributing to the lower-than-desired timber harvest (non-realisation of the planned cutting) in Slovenian private forests. The legal regulation might partially contribute to such a situation. However, average findings from a survey of private forest owners do not indicate that legal regulations are a decisive factor. Nevertheless, there is a critical attitude towards both the normative regulation and its implementation, particularly among some larger private forest owners. When considering legislative changes aimed at increasing timber harvesting, the first and fundamental step is to analyse and develop a policy that considers different approaches for various groups (categories) of private forest owners. This necessitates an examination of the presence of (dis)incentives for timber harvesting in relation to the diverse actual conditions or circumstances of private forest owners. Only on this basis can one formulate different (normative and practical) approaches for addressing the needs of various forest owners categories. Concurrently, it is necessary to acknowledge that many private forest owners own relatively small forest areas, which significantly influences their (mis)management of these forests.
Keywords: gospodarjenje z gozdovi; Slovenija; stvarno pravo; zasebna lastnina; zasebni gozdovi